Phenolic Compounds From the Stems and Leaves of Berchemia lineata (L.) DC - Li, Yitong; Chen, Yu; Xie, Wenli; Li, Xueni; Mei, Gui; Xu, Jing; Zhao, Xiangpei; Teng, Hongli; Yang, Guangzhong (Frontiers in Chemistry, 2022)
Eight new phenolic compounds, named bercheminols A-H (1-8), and eleven known analogues were isolated from the stems and leaves of Berchemia lineata (L.) DC.. Their structures including the absolute configurations were elucidated by extensive spectroscopic analysis, chemical method, and quantum chemical calculations. Compound 1 possesses an unprecedented 3, 4-dihydro-11H-benzo[b]pyrano[4,3-e] oxepin-11-one skeleton. The other new compounds belong to three structural types of natural products, including naphthopyrones (2-5), flavonoids (6-7), and bibenzyl (8). The α-glucosidase inhibitory activities of the isolated compounds were assayed. As a result, vittarin-B (9), rubrofusarin-6-O-β-D-glucopyranoside (11), quercetin (14), kaempferol (15), and dihydrokaempferol (17) showed moderate inhibitory activities against α-glucosidase with IC50 values of 22.5, 28.0, 36.5, 32.7, and 31.9 M, respectively.